Evaluation of Knowledge and Perception of Dental Graduates Regarding Problem-based Learning Method: A Cross-sectional Study - Bhawna Shyamsukha; Amit Reche; Anshu Agrawal; Archana Sonone; Priyanka Paul; Kumar Gaurav Chhabra (Journal of Indian Association of Public Health Dentistry)
Introduction: Problem-based learning (PBL) is an approach to education in medical training that has benefits, such as enhanced information utilization, assimilation of basic and clinical scientific fields. There is a need to compare the training and expertise of college graduates or to scrutinize the influence of PBL on dentistry graduates’ clinical skills. Hence, the study aimed to assess the knowledge and perception of dental graduates attending the PBL curriculum and compare their knowledge and perception among different gender and academic years. Materials and Methods: A cross-sectional study was conducted in a period of 6 months from May 2022 to October 2022 at Dental College, Maharashtra. This study design was planned to assess knowledge and perception of PBL among dental students with a sample size of 315 subjects. An online questionnaire was used and distributed. The questionnaire consisted of 23 statements of which 10 were knowledge based, 10 were for assessment of perception using 5-point Likert scale, and the remaining 3 were open ended. Results: Among 315 dental graduates enrolled for this study, the mean age was 23 ± 0.96 and year-wise mean was 63 ± 0.96.99.3%, 93.6% depicted correct for PBL’s background including elaboration, and theories, respectively. Responses of female students were statistically significant (P = 0.001) than males regarding PBL curriculum and consequently, according to the academic year (P = 0.001) of 1st, 3rd year, and Intern groups compared to 2nd and 4th year. Conclusion: The study emphasized the value of PBL in framework combination coursework and ways, in which it enables students to improve their comprehension, interpretation, and other educational skills.